2002
DOI: 10.1046/j.1365-3156.2002.00940.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of malaria in Afghanistan through social marketing of insecticide‐treated nets: evaluation of coverage and effectiveness by cross‐sectional surveys and passive surveillance

Abstract: SummaryMalaria is often a major health problem in countries undergoing war or conflict owing to breakdown of health systems, displacement of vulnerable populations, and the increased risk of epidemics. After 23 years of conflict, malaria has become prevalent in many rural areas of Afghanistan. From 1993 to the present, a network of non-governmental organizations, co-ordinated by HealthNet International, has operated a programme of bednet sales and re-treatment in lowland areas. To examine whether a strategy ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 16 publications
6
55
0
Order By: Relevance
“…More Beluchi people attended to local Health Services for treatment for In addition, 77.1% of the native resident believed bed nets to be effective in preventing malaria transmission, while the majority of Afghani participants did not believe selfprotection to be effective (Table 3). Similar beliefs and behavior were previously reported in Afghanistan [10]. Nevertheless, the majority of participants and particularly Afghanis did not use bet nets or even window screen.…”
Section: Discussionsupporting
confidence: 82%
“…More Beluchi people attended to local Health Services for treatment for In addition, 77.1% of the native resident believed bed nets to be effective in preventing malaria transmission, while the majority of Afghani participants did not believe selfprotection to be effective (Table 3). Similar beliefs and behavior were previously reported in Afghanistan [10]. Nevertheless, the majority of participants and particularly Afghanis did not use bet nets or even window screen.…”
Section: Discussionsupporting
confidence: 82%
“…There are few data on the effect of ITNs in refugee camps (Rowland et al, 1996) or IDP camps, which are estimated to concentrate more than 21 million people worldwide (USCR, 2000). In east Afghanistan, the year following resettlement, a reduction of 59% (95% CI 25-66%) in P. falciparum parasitaemia was observed among ITN users versus non-users (Rowland et al, 2002). Our evaluation has shown that community-wide distribution of ITNs may be useful for people living in settings such as Bundibugyo, even when the results of the distribution are far from ideal.…”
Section: Discussionmentioning
confidence: 80%
“…Our judgement does not apply to other settings like rural villages in stable conditions where social-marketing of ITN proved to be a good alternative to free distribution (Armstrong Schellenberg et al, 2001;Rowland et al, 2002).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…They possess their own traditional beliefs regarding the causation, transmission, treatment, prevention disease [9]. During 23-year conflict in Afghanistan, more than one-third of the Afghan population (about 6.2 million) fled the war to Pakistan and Iran [10]. The cross-border traffic of Afghanis is an important factor for persistence of malaria in south and southeast of Iran [9].…”
Section: Introductionmentioning
confidence: 99%